2022
DOI: 10.3390/en15082720
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modeling and Control of Dual Active Bridge Converter Considering All Phase-Shifts

Abstract: In the field of power electronics-based electrical power conversion, the Dual Active Bridge (DAB) topology has become very popular in recent years due to its characteristics (e.g., bidirectional operation and galvanic isolation), which are particularly suitable to applications such as interface to renewable energy sources, battery storage systems and in smart grids. Although this converter type has been extensively investigated, its analysis and control still pose many challenges, due to the multiple control v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Based on the results of the analysis of the four working modes of the converter, it can be concluded that the Q EPS and Q SPS expressions of the backflow power are as follows: (10) Equation (10) was subjected to the unitization using (8), from which the backflow power expressions q EPS and q SPS after unitization can be obtained as follows: (11) The q EPS and q SPS three-dimensional plots plotted according to (11) are shown in Figure 5, where k was taken to be 1, 1.5, and 2, respectively. It is known from Figure 5a that there is little inhibitory effect on the backflow power under SPS modulation, and the backflow power increases as k increases.…”
Section: Analysis Of Backflow Powermentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of the analysis of the four working modes of the converter, it can be concluded that the Q EPS and Q SPS expressions of the backflow power are as follows: (10) Equation (10) was subjected to the unitization using (8), from which the backflow power expressions q EPS and q SPS after unitization can be obtained as follows: (11) The q EPS and q SPS three-dimensional plots plotted according to (11) are shown in Figure 5, where k was taken to be 1, 1.5, and 2, respectively. It is known from Figure 5a that there is little inhibitory effect on the backflow power under SPS modulation, and the backflow power increases as k increases.…”
Section: Analysis Of Backflow Powermentioning
confidence: 99%
“…So, a reframing of ( 14) is required. The improved Lagrange method requires that when solving (10), not for the public part η, proceed to elimination and solve for the resulting new D1 expression as follows:…”
Section: Backflow Power Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the determination of phase shifts that minimise peak current has been proposed. The TPS method used for DAB converter control can be found in [11,[23][24][25]. In [23], values of phase shifts in the TPS method were first optimised using the finite control set (FCS) method using a converter model, and implemented using look-up tables.…”
Section: Introductionmentioning
confidence: 99%
“…The TPS method used for DAB converter control can be found in [11,[23][24][25]. In [23], values of phase shifts in the TPS method were first optimised using the finite control set (FCS) method using a converter model, and implemented using look-up tables. In [24], TPS phase shift selection for minimum current stress was performed using AI methods.…”
Section: Introductionmentioning
confidence: 99%